Educational Modules for Increasing Indigenous Australian Students’ Involvement in Chemistry - Scholes, Colin A (Journal of chemical education, 2019)
Indigenous Australians are significantly underrepresented in chemistry based professions, which arises from their low participation in physical science subjects in secondary and tertiary education. This is a multifaceted issue with a number of identified solutions, one of which is to link chemistry with aspects of Indigenous culture. Here, four modules are presented that examine traditional Indigenous Australian practices in detail through a chemistry perspective. These modules assist students to better identify with chemistry principles and therefore encourage further inquiry. The first module is based on toxin removal from plant seeds through water solubility; the second is based on the medicinal properties of the tea tree, which results from isomers of organic compounds. The third module presents color hues of ochre pigments, which are dependent on inorganic chemistry, and the fourth module utilizes plant resin adhesive properties, which are based on glass transition temperatures. These modules have been assessed with Indigenous and non-Indigenous students, who demonstrated increased interest in chemistry. There is also encouraging evidence that these modules have assisted students in taking up additional chemistry subjects.